Unpacking the relationships between emotions and achievement of EFL learners in China: Engagement as a mediator - Wang, Haihua; Wang, Yingli; Li, Shaojie (Frontiers in Psychology, 2023)
Emotions are attracting growing attention in second language acquisition (SLA), especially with the advent of positive psychology (PP). The fundamental role of emotions in affecting learners’ second language (L2) achievement has been well documented. Evidence also indicates that emotions can significantly influence learners’ L2 learning engagement which profoundly impacts their academic performance. However, the links between emotions, engagement and L2 achievement remain underexplored. To contribute to this research domain, the present study sought to unpack the relationships between learners’ emotions, such as foreign language enjoyment (FLE), foreign language classroom anxiety (FLCA) and foreign language learning boredom (FLLB), and engagement as well as their English achievement. A total of 907 learners of English as a foreign language (EFL) from a university in China were recruited to complete an online questionnaire. Structural equation modeling (SEM) was performed to test the hypothesized relations among the variables. Results revealed correlations between learners’ FLE, FLCA and FLLB. Furthermore, learners’ engagement was found to mediate the relationships between their emotions (FLE, FLCA, and FLLB) and actual English achievement. The findings broaden the nomological network of emotions and engagement in the EFL context, and provide evidence for the mechanism underlying the relationships between emotions, engagement and achievement, thereby shedding light on EFL teaching and learning at the tertiary level in China.